TANTANGAN GURU SEKOLAH DASAR DALAM BERINOVASI UNTUK MEMBENTUK KARAKTER SISWA DI ERA KURIKULUM MERDEKA - Dinda Fajar Chairani; Nazwa Nursakinah; Novelia Rhamadani; Rifqa Gusmida Barokah (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
This study aims to explore the challenges faced by primary school teachers in innovating to shape pupils’ character in the era of the Merdeka Curriculum, as well as the adaptive strategies they have developed in response to these challenges. The study employs a phenomenological qualitative approach using semi-structured in-depth interviews with three primary school teachers selected through purposive sampling. Data were analysed using the Miles & Saldaña interactive model through three stages of coding: open coding, axial coding, and selective coding. Data validity was ensured through source triangulation and member check. The research findings revealed six main themes: (1) internal challenges faced by teachers, such as time constraints, hesitation to innovate, and heterogeneity in pupils’ abilities; (2) limitations in facilities and infrastructure, particularly unequal access to technology; (3) weak parental involvement and inconsistencies between parenting styles and school values; (4) teachers’ adaptive strategies through gradual innovation, varied methods, and contextual adjustments; (5) institutional support through professional learning communities (KKG) and the Merdeka Mengajar Platform; and (6) teachers’ hopes for a reduction in administrative burdens, practical training, and greater policy flexibility. This study concludes that the successful development of student character in the era of the Merdeka Curriculum requires synergy between teachers’ professional readiness, the support of the school ecosystem, parental involvement, and policies that prioritise the real needs of teachers in the field.